Aldehyde‐forming fatty acyl‐CoA reductase from cyanobacteria: expression, purification and characterization of the recombinant enzyme. (23rd August 2013) - Lin, Fengming; Das, Debasis; Lin, Xiaoxia N.; Marsh, E. Neil G.
<x xml:space="preserve">Abstract</x> Long‐chain acyl‐CoA reductases (ACRs) catalyze a key step in the biosynthesis of hydrocarbon waxes. As such they are attractive as components in engineered metabolic pathways for 'drop in' biofuels. Most ACR enzymes are integral membrane proteins, but a cytosolic ACR was recently discovered in cyanobacteria. The ACR from Synechococcus elongatus was overexpressed in Escherichia coli, purified and characterized. The enzyme was specific for NADPH and catalyzed the reduction of fatty acyl‐CoA esters to the corresponding aldehydes, rather than alcohols. Stearoyl‐CoA was the most effective substrate, being reduced more rapidly than either longer or shorter chain acyl‐CoAs. ACR required divalent metal ions, e.g. Mg2+, for activity and was stimulated ~ 10‐fold by K+. The enzyme was inactivated by iodoacetamide and was acylated on incubation with stearoyl‐CoA, suggesting that reduction occurs through an enzyme‐thioester intermediate. Consistent with this, steady state kinetic analysis indicates that the enzyme operates by a 'ping‐pong' mechanism with kcat = 0.36 ± 0.023 min−1, Km (stearoyl‐CoA) = 31.9 ± 4.2 μm and Km (NADPH) = 35.6 ± 4.9 μm. The slow turnover number measured for ACR poses a challenge for its use in biofuel applications where highly efficient enzymes are needed.